PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI BADAN KESATUAN BANGSA DAN POLITIK KOTA SEMARANG - Shabrina Anita Sari; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Problems in this study were less than optimal performance of employees at the Badan Kesatuan Bangsa Dan Politik Kota Semarang. The purpose of this study was to determine how much influence the work ability and work motivation on employee performance. This study uses a quantitative research with respondents a number of 33 employees are all employees of Badan Kesatuan Bangsa Dan Politik Kota Semarang. The sampling technique used is the technique of the census. The analytical tool used in this study is the Rank Correlation Coefficient Kendall, Kendall Konkordasi coefficient, and the coefficient of determination. Results from this study indicate that there is a positive and significant influence between the variables of work ability (X1) with employee performance (Y) with correlation coefficient 0.335 amounting to KD 2.741 at 11.22%; there is a positive and significant influence between the variables of work motivation (X2) with employee performance (Y) with correlation coefficient 0,331 and with a KD of 10.95%; and there are two variables influence work ability and work motivation on employee performance amounted to KD 69.12 by 29.16%. The conclusion from this study is that the performance of employees in the Badan Kesatuan Bangsa Dan Politik Kota Semarang has been good, the ability to work in the Badan Kesatuan Bangsa Dan Politik Kota Semarang has been good, and motivation to work in the Badan Kesatuan Bangsa Dan Politik Kota Semarang is good. The advice given is conducting training to all employees, inculcate discipline, reward and punishment, inculcate cooperation, and more diffuse leaders to subordinates.